Analysis of ShuffleNets with limited number of wavelength converters employing deflection routing - Castanon, Gerardo; Low, Andy L. Y.; Chien, Su Fong; Koa, Chong Gee; Bonon, Alberto (Optica Publishing Group, 2005)
Optical node performance analysis in terms of number of wavelength converters for a multihop optical ShuffleNet under deflection routing is presented. From the computed results for a given number of wavelengths, it is found that in order to achieve the minimum deflection probability at full load, the number of wavelength converters required is at most 60% of the number of wavelengths. Any additional wavelength converters would not be necessary in reducing the overall deflection probability. These upper-bound findings are indeed helpful for network engineers designing a cost-effective network node. (c) 2004 Optical Society of America.